Systemic Identification and Functional Characterization of Common in Fungal Extracellular Membrane Proteins in Lasiodiplodia theobromae - Peng, Junbo; Wu, Linna; Zhang, Wei; Zhang, Qi; Xing, Qikai; Wang, Xuncheng; Li, Xinghong; Yan, Jiye (Frontiers in Plant Science, 2021)
Plant pathogenic fungi deploy secreted proteins into apoplastic space or intracellular lumen to promote successful infections during plant-pathogen interactions. In the present study, fourteen CFEM domain-containing proteins were systemically identified in Lasiodiplodia theobromae and eight of them were functionally characterized. All eight proteins were confirmed to be secreted into extracellular space by a yeast signal peptide trapping system. The transcriptional levels of most CFEM genes, except for LtCFEM2 and LtCFEM6, were significantly elevated during infection. In addition, almost all LtCFEM genes, apart from LtCFEM2, LtCFEM3, and LtCFEM6, were transcriptionally up-regulated at 35℃ in contrast to that at 25℃ and 30℃. As two elicitors, LtCFEM1 induced local yellowish phenotype and LtCFEM4 triggered cell death in Nicotiana benthamiana leaves. Furthermore, these proteins displayed distinct subcellular localizations when expressed transiently in N. benthamiana. Moreover, two genes, LtCFEM7 and LtCFEM8, were found to be spliced alternatively by RT-PCR and sequencing. Therefore, our data suggest that LtCFEM proteins play important roles in multiple aspects, including pathogenicity and plant immune response, which will enhance our understanding of the sophisticated pathogenic mechanisms of plant opportunistic pathogen L. theobromae.